2014
DOI: 10.3329/bjpp.v26i1-2.19958
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic parameters of Amoxicillin in Bangladeshi volunteers: a preliminary evaluation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The pharmacokinetic status of Bangladeshi population is still not very clearly understood, though couple of studies revealed that orally administered medicines achieve adequate concentration to demonstrate desired pharmacological effects (Chowdhury et al, 2010;Chowdhury et al, 2011;Chowdhury et al, 2014). The present study was not designed to ascertain or clarify the correlation of kinetics with dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic status of Bangladeshi population is still not very clearly understood, though couple of studies revealed that orally administered medicines achieve adequate concentration to demonstrate desired pharmacological effects (Chowdhury et al, 2010;Chowdhury et al, 2011;Chowdhury et al, 2014). The present study was not designed to ascertain or clarify the correlation of kinetics with dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Though some initiative and effort was made towards understanding the pharmacokinetics of antimicrobials in Bangladeshi children 22 and adult population [23][24] , very little development has been achieved. There were different challenges like selection of volunteers, laboratory facilities, establishment of laboratory methods and hospitalization of volunteers, for which this type of pharmacokinetic study could not be conducted before in this region.…”
Section: Introductionmentioning
confidence: 99%